Bài tập  /  Bài đang cần trả lời

Giải bài có thưởng!

Rút gọn các biểu thức

16/  1/2.x+1/6.x(x-2)=3/4-2.x

19/  5/12.x+3=1/3-7/12.x

20/  1/2.x+5/2=7/2.x-3/4

 

0 Xem trả lời
Hỏi chi tiết
74
Tham khảo câu trả lời từ Trợ lý ảo Lazi
To solve these equations, we will simplify each equation step by step and isolate the variable.

1) 16/(1/2)x + (1/6)x(x-2) = 3/4 - 2x

First, let's simplify the left side of the equation:
16/(1/2)x can be rewritten as 16 * 2/x = 32/x
(1/6)x(x-2) can be expanded as (1/6)x^2 - (1/3)x

Now, let's rewrite the equation:
32/x + (1/6)x^2 - (1/3)x = 3/4 - 2x

To get rid of the fractions, let's multiply the entire equation by the least common denominator (LCD), which is 12x:
12x * (32/x) + 12x * ((1/6)x^2 - (1/3)x) = 12x * (3/4 - 2x)

Simplifying further:
384 + 2x^3 - 4x^2 - 4x = 9x - 24x^2

Rearranging the terms:
2x^3 - 4x^2 - 4x + 9x - 24x^2 - 384 = 0

Combining like terms:
2x^3 - 28x^2 + 5x - 384 = 0

Unfortunately, this equation does not have a simple solution. You may need to use numerical methods or a graphing calculator to find an approximate solution.

2) 19/(5/12)x + 3 = 1/3 - (7/12)x

First, let's simplify the left side of the equation:
19/(5/12)x can be rewritten as 19 * 12/5x = 228/5x

Now, let's rewrite the equation:
228/5x + 3 = 1/3 - (7/12)x

To get rid of the fractions, let's multiply the entire equation by the least common denominator (LCD), which is 60x:
60x * (228/5x) + 60x * 3 = 60x * (1/3) - 60x * (7/12)x

Simplifying further:
456 + 180x = 20 - 35x^2

Rearranging the terms:
35x^2 + 180x + 456 - 20 = 0

Combining like terms:
35x^2 + 180x + 436 = 0

Unfortunately, this equation does not have a simple solution. You may need to use numerical methods or a graphing calculator to find an approximate solution.

3) 20/(1/2)x + 5/2 = 7/2x - 3/4

First, let's simplify the left side of the equation:
20/(1/2)x can be rewritten as 20 * 2/x = 40/x

Now, let's rewrite the equation:
40/x + 5/2 = 7/2x - 3/4

To get rid of the fractions, let's multiply the entire equation by the least common denominator (LCD), which is 4x:
4x * (40/x) + 4x * (5/2) = 4x * (7/2x) - 4x * (3/4)

Simplifying further:
160 + 10x = 14 - 3x

Rearranging the terms:
10x + 3x = 14 - 160

Combining like terms:
13x = -146

Dividing both sides by 13:
x = -146/13

Therefore, the solution to the equation is x = -146/13.

Bạn hỏi - Lazi trả lời

Bạn muốn biết điều gì?

GỬI CÂU HỎI
Học tập không giới hạn cùng học sinh cả nước và AI, sôi động, tích cực, trải nghiệm

Hôm nay bạn thế nào? Hãy nhấp vào một lựa chọn, nếu may mắn bạn sẽ được tặng 50.000 xu từ Lazi

Vui Buồn Bình thường
×
Trợ lý ảo Trợ lý ảo
Gửi câu hỏi
×